Corporate Governance, Risk Management, and Financial Performance: The Mediating Role of Risk Governance in Indonesia's Islamic Banks - Fauziah Fauziah; Nur Atiqah; Pratiwi Kurniati; Prihantono Prihantono; Mohd. Shahrul Komaruddin (Shirkah: Journal of Economics and Business, 2025)
Islamic banks face increasing pressure to strengthen governance and risk oversight, yet the mediating role of risk governance in financial performance remains underexplored, particularly in Indonesia. This study aims to examine the structural relationships among corporate governance, risk management, risk governance, and the financial performance of Indonesia’s Islamic banks. A quantitative research, drawing on secondary data from annual reports of eight Islamic banks between 2016 and 2023 with 64 observations, was employed. Corporate governance was measured using a composite governance index, risk governance through committee structures, risk management via credit, operational, liquidity, and Sharia-compliance controls, while financial performance was proxied by ROA and ROE. Data were analyzed using path analysis with PLS-SEM. The findings reveal that corporate governance significantly strengthens risk governance but does not directly improve financial performance. Conversely, risk management exerts a significant positive influence on financial performance, though it does not shape risk governance. Risk governance itself neither impacts financial performance nor mediates the relationships between governance, risk management, and performance. These results suggest that risk governance in Indonesian Islamic banks remains compliance-oriented rather than performance-enhancing. The study highlights the need for regulatory reforms and strategic integration of risk governance to support sustainable growth.